Dynamic Characteristics of Screen Mesh in Drilling Vibration Screens under Ultrasonic Compound Action - Fang, Qingzheng; Hou, Yongjun (Scientific Journal of Technology, 2026)
Screen mesh is the core component of drilling vibration screens and a key consumable part in the field of drilling engineering. Traditional vibration screens generally suffer from technical bottlenecks such as low screening efficiency and frequent screen clogging in the screening of fine-grained materials. With the continuous development of screening technology, various technical solutions to alleviate screen clogging have been proposed successively, among which ultrasonic vibration-assisted screening is a relatively advanced technical form. Taking the screen mesh of drilling vibration screens under ultrasonic compound action as the research object, this paper systematically carries out dynamic modeling and finite element simulation analysis on the frameless single-layer screen mesh structure, and investigates the free vibration, mechanical vibration and ultrasonic-mechanical compound vibration characteristics of the screen mesh. It aims to reveal the dynamic mechanism of the screen mesh under ultrasonic-mechanical compound vibration, and provide theoretical support for the structural optimization design and engineering application of ultrasonic vibration screens.